Evaluasi Kesuksesan Implementasi Multimedia Auto Recording Smart Hybrid Classroom Menggunakan Delone and Mclean's Model (Studi Pada Fakultas Ilmu Komputer Universitas Brawijaya) - Savero Muhammad Syahrizal; Yusi Tyroni Mursityo; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
MASH Classroom is a smart class technology implemented by FILKOM UB to present multimedia-based teaching media. But in implementation, it still has problems related to the successful implementation according to FILKOM UB students. Therefore it is necessary to evaluate the implementation of MASH Class to obtain findings and recommendations to increase the level of successful implementation. Evaluation was carried out using six variables contained in Delone and Mclean Model which included system quality, information quality, service quality, system usage, user satisfaction, and net benefits. The study used a quantitative method with descriptive statistical analysis method with the involvement of 105 respondents. Data obtained from this study was obtained from the distribution of online questionnaires. The results of system quality variable is 54.33%, information quality is 59.83%, service quality is 70.94%, system use is 60.17%, user satisfaction is 55.50%, and net benefit is 57.37% . From the results obtained from the contribution to improve the success of the implementation of the MASH Classroom system including the application of interactive systems that can support interaction in the implementation of learning in different classes, making instruction manuals that provide information regarding system usage, as well as standardization and service customization provided at students related to system implementation, as well as making learning designs.